(untitled) (Natural Resources and Technology, 2024)
The knowledge of all water resources, today, is a basic prerequisite for existence and further development of the society. Over 80% of the water supply to the population and industry in the Republic of Macedonia is provided through the capture of underground water. Since for regional water supply systems it is necessary to invest enormous funds, mainly for the construction of surface reservoirs, solving the problem of water supply at the sub-regional, municipal or local level practically gains greater importance, among other things, due to the rational conditions of the construction and maintenance of the systems. In that sense, the municipality of Sveti Nikole is an example of very high-quality approach to research for the needs of finding local potential conditions for public centralized water supply in individual settlements or parts of municipal territories, and thus rational and thoughtful investments for the future. In this paper, the potential opportunities for capturing economically viable amounts of underground water in Neogene sediments are highlighted, based on the results of the hydrogeological research. Based on the specified parameters, the environment is characterized by a filtration coefficient EB – 1 - K = 5.00 × 10-5 m/s, EB – 2 - K = 1.7 × 10-5 m/s, coefficient of water permeability EB – 1 - T = 2.22 × 10-4 m2/s = 23 m2/day. EB – 2 - T = 7.5 × 10- 4 m2/s = 24 m2/day and yield Qexp for EB-1 - 1.47 l/s, Qexp for EB – 2 = 1.07 l/s